Contemporary Migration to South Africa : A Regional Development Issue - Segatti, Aurelia; Landau, Loren B. (World Bank, 2012)
This book is a call to rethink migration regimes in Southern Africa in ways that are more explicitly developmental and focused on poverty. Current policy debates are devoted almost exclusively to border control and policing; they pay only lip service to local and regional developmental strategies. This volume takes a different approach. Its contributors are scholars who are convinced that empirically based policy making stands a better chance of succeeding than untested preconceptions that risk reproducing recipes that have failed elsewhere. The book is therefore strong on empirics, providing a wealth of original data. It also reframes existing approaches and reexamines secondary data from fresh perspectives. Although the focus remains South Africa, the book reflects South Africa's regional role and draws on data from across the Southern African Development Community (SADC). This book broadens the 'migration' agenda beyond the boundaries of migration studies and migration policy silos. This book is intended to become a resource for a range of audiences in Southern Africa and the continent.